Multi-locus sequence types of Mycoplasma bovis isolated from Ontario, Canada in the past three decades have a temporal distribution. (January 2018) - Bell-Rogers, Patricia; Parker, Lois; Cai, Hugh Y.
A total of 217 Mycoplasma bovis isolates cultured from clinical cases in Ontario, Canada, over the past 30 y were selected to be characterized by a multi-locus sequence typing (MLST) method. Eleven housekeeping genes were evaluated for suitability for MLST; 2 loci that had been used in prior MLST schemes, dnaN and metS, along with hsp70 were chosen for further sequence analysis. The remaining loci— adk, efp, gmk, gyrB, polC, rpoB, tpiA, and uvrC genes—were not used because they had little to no sequence variation. The sequence data from the chosen loci ( dnaN, hsp70, metS ) generated 28 sequence types (STs), with the 3 loci having 15, 5, and 7 alleles, respectively. These molecular typing results revealed that the STs had a temporal distribution; over the course of 3 decades, some STs disappeared and new STs appeared. Recent isolates had a greater variety of STs, which may indicate that new strains are emerging more rapidly now than in the past.